Two New ‘Bottletail Squids’ (Cephalopoda: Sepiadariidae) from New Zealand, with New Observations on Sepioloidea pacifica (Kirk, 1882) - Santos, Jaever Marcel (Auckland University of Technology, 2021)
Members of the cephalopod family Sepiadariidae, sometimes called ‘bottletail squids’, are known exclusively from the Indo-Pacific and southwest Pacific. To date, only one nominal species has been described from New Zealand waters: Sepioloidea pacifica (Kirk, 1882). However, researchers have long suspected the presence of additional Sepioloidea species. Herein, the majority of known Sepioloidea material from New Zealand national collections was examined; both morphological, and, where available, molecular characters were compared. As a result, this thesis describes two new species (Sepioloidea n. sp. 1, and Sepioloidea n. sp. 2) using this integrative taxonomic approach, with relevant features of Sepioloidea pacifica redescribed and illustrated for comparison. Sepioloidea n. sp. 1 is distinguished from its congeners by its tentacular club sucker arrangement (transverse rows of ten suckers), hectocotylus structure, and relatively large size at maturity (to ~56 mm mantle length). The distal ~25% of the hectocotylus is modified with ~15 pairs of distinct spire- and tongue-shaped lappets. In Sepioloidea n. sp. 2 the tentacular club suckers are in transverse rows of six or seven suckers and females possess ruffled buccal membrane. The hectocotylised arm is modified distally along 50% of its length with ~16 pairs of globular-tipped spire-shaped lappets. Molecular data support these morphological differences, with the minimum interspecific distance (11.09 %) being far greater than the maximum intraspecific distance (1.57 %) for COI (cyctochrome c oxidase subunit I). Some differences in collection depth are also apparent, with S. n. sp. 1 collected at depths of 73–911 m, while S. n. sp. 2 has been collected at depths of 0–440 m, and present data support S. pacifica being a shallow-dwelling species, known from depths of 0–55 m. These findings triple the known diversity of Sepioloidea in New Zealand waters and nearly double the number of known species in the genus.
Keywords: cephalopoda; sepiadariidae; sepioloidea; sepiolida; Taxonomy; Bottletail squid; Southwest Pacific